The Effectiveness of Case-Based History Learning in Developing Students' Research and Problem-Solving Skills - Mutawakkil, Mutawakkil (Eastasouth Institute, 2024)
This study aims to explore the effectiveness of case-based learning in history education in developing students' research and problem-solving skills. A literature review method was employed to critically analyze relevant sources. The findings indicate that case-based learning positively impacts students' analytical and research skills and enhances their motivation to learn. Through the case study approach, students are trained to explore information sources independently, analyze data, and formulate arguments based on relevant evidence. Additionally, case studies enable students to confront complex situations, encouraging them to think critically and creatively when searching for solutions. These findings suggest that case-based learning not only improves students' understanding of historical events but also enriches their learning experience in a contextual and applicable way. This research aims to contribute to the development of more innovative history teaching methods in schools and provides practical implications for teachers in enhancing students' critical thinking skills.